Novel metal foam and phase change material integrated multi-tube heat exchanger design for simultaneous charging and discharging - Yadav V.K.; Jee M.; Sarkar J.; Ghosh P. (My University, 2025)
The triplex tube heat exchanger utilizing the phase change material (PCM) plays a crucial role in various energy storage/transfer applications; however, it suffers from long charging/discharging time, so charging/discharging time reduction by enhanced design is an emerging concern. Therefore, a novel PCM-inserted multi-tube heat exchanger with dual-side charging along with multiple discharging is proposed and analyzed using the non-equilibrium model for three different embeddings: PCM, fin & PCM, and metal foam & PCM, under only charging/discharging as well as simultaneous charging-discharging modes. The foam & PCM case has the shortest melting time, nearly 70 % and 75 % shorter than the fin & PCM and only PCM, respectively. The average temperature and melting fraction values are also the highest (378.8 K and 0.875, respectively) for the foam & PCM under simultaneous charging-discharging mode. Energy stored and energy output are also maximum for the foam-PCM (nearly 8 % and 22 % higher than fin-PCM but 15.5 % and 263 % more than only PCM, respectively). Variation in charging and discharging fluids inlet temperatures significantly influences the melting fraction and energy output (62 % change for charging within the tested operating range). The variation in the foam porosity from 90 to 98 % also has a notable impact (nearly 7 % decrease) on the energy output. Hence, the proposed foam and PCM-embedded heat exchanger is recommended to overcome the intermittent nature of solar energy with rapid response. © 2025 Elsevier Ltd